Tafsir Metafisika Sufisme tentang Penciptaan Perempuan - Hendri, Novi (Research and Development Institution, Darussalam Institute for Islamic Studies, 2018)
This research aims to elaborate ideas about the creation of women in the perspective of Sufism metaphysics. The study uses text analysis methods, especially Sufism metaphysical texts. The texts on the creation of women in a number of Sufism literature are critically analyzed. The results show that apart from theology and fiqh, Sufism offers a space of creative feminism about interpretation. Sufism's metaphysical interpretation of the creation of women focuses more on cosmological and metaphysical aspects. Ibn 'Arabi and Jalaluddin al-Rumi with their creative interpretations gave more appreciation to feminism. They even give and respect women's positions that reflect God's creativity. Seeing God in women means seeing God Himself.